Remediation of hydrocarbon contaminated soil using alkyl benzene sulfonate: preliminary study - Monik Kasman; H Hadrah; Salmariza Sy (Institution for Industrial Research and Standardization of Industry - Padang, 2021)
This work was aimed to remediate petroleum contaminated soil by soil washing method. This method is among alternative remediation used to remove petroleum pollutant or contaminant from soil using aqueous chemical surfactan. This studi was preceeded to the characterization of contaminated soil to classify the soil including gain size, oil and gease and Total Petroleum Hydrocarbon (TPH). Laboratory scale experiment was done to investigate the effect of aqueous chemical surfactan Alkyl Benzena Sulfonate (ABS). The effect of surfactant and bulking agent to TPH removal was observed by varying the ratio of contaminated soil (g) to bulking agent (silica soil) in g/g units, with the ratio 50:50; 35:65 and 25:75 in variations of surfactant solution . 0%; 0.25%; 0.5%; 0.75% and 1.0% (mL/mL). The results showed that the soil washing was influenced by bulking agent ratio. The higher the ratio of the bulking agent, the higher the TPH reduction. The highest percentage of TPH removal achieved 92%, at surfactant concentration of 0.25% and ratio of soil/bulking agent of 25 : 75.